A framework for realizing universal standardization for internet of things - Usman, Mohammed Joda; Xing, Zhang; Haruna, Chiroma; Abubakar, Adamu; Ya'u Gital, Abdusalam (Engineering and Technology Publishing (ETP), 2014)
Internet of Things is a paradigm referring to the pervasive presence of a network of things and objects that are able to interact, and cooperate with each other. This paradigm also suggests that in the future these objects can produce large amount of data to the Internet, and other network applications. It was predicted that the amount of data produced by things can exceed data produced by human in the near future due to rapid advancements in technology. At present, realizing truly Internet of Things is hindered by differences in government policies. In order to eliminate the limitation hindering the actualization of the Internet of Things, we proposed a framework that might lead to the universal standardization of the Internet of Things. With little additional information, our proposal has the potentials of being use to totally circumvent the current limitations.